2015
DOI: 10.1007/s10899-015-9536-z
|View full text |Cite
|
Sign up to set email alerts
|

Problem Gambling Associated with Violent and Criminal Behaviour: A Danish Population-Based Survey and Register Study

Abstract: This study compares the number of criminal charges among problem gamblers (N = 384) and non-problem gamblers including non-gamblers (N = 18,241) and examines whether problem gambling is more strongly associated with income-generating crimes like theft, fraud and forgery than other types of crimes such as violent crimes. A cohort study was carried out, based on data from the Danish Health and Morbidity Surveys in 2005 and 2010, which were linked at the individual level with data from The Danish National Crimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 26 publications
0
38
0
2
Order By: Relevance
“…Additionally, the relatively recent emergence of studies suggesting that the rate of violent gambling-related crime might also be higher than in non-gambling populations (Rudd & Thomas, 2016;Laursen, Plauborg, Ekholm, Larsen, & Juel, 2016;Turner, Preston, Saunders, McAvoy, & Jain, 2009) may be symptomatic of a wider underestimation of the prevalence of violent gambling-related crimes in the literature. While it is probable that many of these violent crimes were financiallymotivated, the broad range of offences committed by participants across these studies necessitated the consideration of other influences beyond financial motivations, for example, risk-taking (Rudd & Thomas, 2016;Laursen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, the relatively recent emergence of studies suggesting that the rate of violent gambling-related crime might also be higher than in non-gambling populations (Rudd & Thomas, 2016;Laursen, Plauborg, Ekholm, Larsen, & Juel, 2016;Turner, Preston, Saunders, McAvoy, & Jain, 2009) may be symptomatic of a wider underestimation of the prevalence of violent gambling-related crimes in the literature. While it is probable that many of these violent crimes were financiallymotivated, the broad range of offences committed by participants across these studies necessitated the consideration of other influences beyond financial motivations, for example, risk-taking (Rudd & Thomas, 2016;Laursen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Rudd and Thomas (2016) found that potential problem gamblers committed crimes for financial gain at a higher rate than non-problem gamblers; however, they also demonstrated elevated rates of violent crimes such as robbery. Similarly, Laursen, Plauborg, Ekholm, Larsen, and Juel (2016) found that problem gamblers were significantly more likely than non-problem gamblers to be charged with both economic and violent crimes, and no more likely to be charged with one type than the other. Notably, in this study, violent crimes were not necessarily income-generating (Laursen et al, 2016).…”
Section: The Nature Of Gambling-related Crimementioning
confidence: 92%
See 3 more Smart Citations